Subfertility, reproductive endocrinology and assisted reproduction - Stewart, Jane A. (Cambridge University Press, 2019)
"A good fertility clinic is about more than success rates, and a good fertility specialist has an understanding of fertility problems which goes beyond the clinical aspects of patient care"--Provided by publisher
Includes bibliographical references and index
Keywords: Infertility; Reproductive Techniques, Assisted; Endocrine System Diseases -- complications; Reproductive Medicine -- methods